Manajemen Program Tahfizh Menginap Sebagai Upaya Pembiasaan Karakter Religius Santri - Fitria, Nur Aidila; Julyanur, Muhammad Yoga; Nabila, Alawiyah; Pariati, Ema; Laila, Ida (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2023)
Shaping the character of students towards better personalities is not an easy thing, especially in today's sophisticated era with the use of technology and information such as gadgets. This is certainly a challenge for Al-Qur'an education. This research was meant to analyze the planning, implementation, and evaluation of the “Tahfizh Menginap” program as an effort to habituate the religious character of the students at Rumah Ridhotullah Sangatta Qur'an Sangatta Utara. This research used a qualitative approach with descriptive research type, where the data described by the author is data obtained through unstructured interviews. The result is that the Tahfizh Menginap Program is designed and structured by involving educators, students, and of course various learning materials. In its implementation, the Tahfizh Menginap program teaches students a lot about daily practices that students hope to practice in their daily lives. Finally, some students already have a brave, independent attitude, and always implement the knowledge they have acquired in their daily life. Meanwhile, some others are still trying and trying to be able to do the same thing. For this reason, educators need to evaluate this program so that in the future it can be even better